A escola e a educação para a infância na perspectiva de uma educação integral - Penteado, Juliana Faria Góes (2018)
This research has as object of study the school, the child and the education for the childhood in the perspective of comprehensive education. For this, the qualitative approach was used as a methodology which seeks to obtain reliable information to explain in depth the meaning and characteristics of the object of study, based on bibliographic research and documental analysis. Sixteen documents based on the Brazilian Federal Constitution, the Statute of the Child and the Adolescent and the Law on the Guidelines and Bases for the Brazilian Education were searched, which triggered a broader research on the subject. Thus, the analysis had as reference the concept of comprehensive education in the full-day school, which implies the mobilization of educational energies in the modification of the school curriculum model in which the actions foresee the child in its entirety, based on Moll (2010, 2012). To that end, the history of childhood and its place in today's society were studied (ARIÈS, 1975; CORSARO, 2011; STEARNS, 2006), the role of the school (GIRALDELLI, 1996; LIBÂNEO; OLIVEIRA; TOSCHI, 2008; SAVIANI, 2008, 2013) and the school curriculum aspects (SILVA, 1999; SACRISTÁN, 2013; RICHTER & BARBOSA, 2010). By means of these surveys, it was possible to create the articulation needed to analyze the ways throughout which the public policies for childhood are being formed in the sense of providing comprehensive education for children in early childhood education, more specifically for 4-5 year olds, which, after the Law No. 12,796/2013, became part of compulsory basic education. It is concluded that recent studies on childhood had great impact on public policies for early childhood education, highlighting the child in its entirety. It is also observed that the concept of comprehensive education appears in most documents. However, this study emphasizes that, although comprehensive education is foreseen, actions that effectively materialize such education are just a few and do not express the commitment to the democratization and the implementation of comprehensive early childhood education